2006
DOI: 10.1111/j.1471-4159.2006.04036.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β induces the expression of aquaporin‐4 through a nuclear factor‐κB pathway in rat astrocytes

Abstract: Interleukin (IL)-1b is known to play a role in the formation of brain edema after various types of injury. Aquaporin (AQP)4 is also reported to be involved in the progression of brain edema. We tested the hypothesis that AQP4 is induced in response to IL-1b. We found that expression of AQP4 mRNA and protein was significantly up-regulated by IL-1b in cultured rat astrocytes, and that intracerebroventricular administration of IL-1b increased the expression of AQP4 protein in rat brain. The effects of IL-1b on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 48 publications
(47 reference statements)
4
76
1
Order By: Relevance
“…S5). Contrary to the findings of Ito et al (29), Tourdias et al (30) showed opposing IL1␤ and AQP4 profiles in animal models. They reported that in inflammatory animal models IL1␤ expression in the brain peaked at day 1 and dropped back to basal levels by day 7.…”
Section: Mir-130a Represses Transcriptional Activity Of Aqp4 M1contrasting
confidence: 54%
See 1 more Smart Citation
“…S5). Contrary to the findings of Ito et al (29), Tourdias et al (30) showed opposing IL1␤ and AQP4 profiles in animal models. They reported that in inflammatory animal models IL1␤ expression in the brain peaked at day 1 and dropped back to basal levels by day 7.…”
Section: Mir-130a Represses Transcriptional Activity Of Aqp4 M1contrasting
confidence: 54%
“…(29) showed that increasing the interleukin-1␤ (IL1␤) concentration could mediate transcriptional activation of the AQP4 M1 promoter via the transcription factor nuclear factor B (NFB). However, no NFB binding site was identified on the AQP4 M1 promoter, suggesting an indirect effect by the transcription factor (29). We observed that removal of IL1␤ from cultured cells did not significantly affect AQP4 M1 expression.…”
Section: Mir-130a Represses Transcriptional Activity Of Aqp4 M1mentioning
confidence: 99%
“…Second, LPS may act indirectly; these indirect effects may be mediated by LPS-induced pro-inflammatory cytokines, such as interleukin (IL)-1β. A previous study has demonstrated that IL-1β induces the expression of AQP4 through IL-1 receptor in rat primary astrocytes [7]. In the anterior pituitary gland, robust IL-1β mRNA induction has been demonstrated at 0.5 hr after peripheral LPS injection [16,19].…”
mentioning
confidence: 90%
“…Moreover, this transcription factor seems to regulate the expression of some AQPs and, in turn, control cell proliferation. [104][105][106][107] In addition, hypoxia-inducible trans-cription factors, HIF-1a or 2a, may take part in the proliferation mediated by AQPs. We have shown that stable overexpression of AQP1, 3 and 5 increases the stability of HIF-2a during chronic exposure to hypoxia 108,109 thereby increasing the expression of many genes implicated in activities relevant for tumor growth, such as glucose uptake and metabolism, angiogenesis, cell proliferation and apoptosis.…”
Section: Cross-talk Between Transcription Factors Cytokines and Aqpsmentioning
confidence: 99%